2013
DOI: 10.3389/fpsyg.2013.00377
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “somatization” and “psychologization”: symptom-level variation in depressed Han Chinese and Euro-Canadian outpatients

Abstract: The finding that people of Chinese heritage tend to emphasize somatic rather than psychological symptoms of depression has frequently been discussed in the culture and mental health literature since the 1970s. Recent studies have confirmed that Chinese samples report more somatic and fewer psychological depression symptoms compared to “Western” samples. The question remains, however, as to whether or not these effects are attributable to variation in all the constituent symptoms or to a subset. If the latter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 42 publications
7
59
3
Order By: Relevance
“…This observation has since been empirically supported in several cross-cultural studies (Parker et al, 2001;Ryder et al, 2008;Zhou et al, 2011;Dere et al, 2013) comparing Chinese and 'Western' participants. Ryder and Chentsova-Dutton (2012) proposed that cultural scripts for distress and normative assumptions about symptoms and syndromes in a given cultural context might help shape the experience and expression of depression.…”
Section: Introductionmentioning
confidence: 64%
“…This observation has since been empirically supported in several cross-cultural studies (Parker et al, 2001;Ryder et al, 2008;Zhou et al, 2011;Dere et al, 2013) comparing Chinese and 'Western' participants. Ryder and Chentsova-Dutton (2012) proposed that cultural scripts for distress and normative assumptions about symptoms and syndromes in a given cultural context might help shape the experience and expression of depression.…”
Section: Introductionmentioning
confidence: 64%
“…It is proposed that social identity theorizing (Tajfel & Turner, 1979;Turner, 1991) With this in mind, in Chapters 3 and 4, we shift attention to studying depression in Western cultures. This is in line with recent work contending that the very concept of somatization rests on the cultural assumption that psychological symptoms are more central to depression, and has thus focused on Western psychologization (Dere et al, 2013;Ryder et al, 2008). More specifically, this research has suggested that psychologization among Westerners represents the larger and more consistent effect, raising the possibility that this may be more culturally specific than Asian somatization (Ryder et al, 2008).…”
Section: Thesis Overviewsupporting
confidence: 86%
“…Despite extensive investigation of somatization of depression (e.g., Dere et al, 2013;Ryder et al, 2008;Simon et al, 1999;Yen, Robins, & Lin, 2000), much of this work has perhaps focused too strongly on the question of whether Asians somaticize.…”
Section: Thesis Overviewmentioning
confidence: 99%
“…This is one of a few studies using a nationally representative community sample of Asian and Euro pean Americans that examines both somatic and psychological symptoms. Moreover, with the exception of Uebelacker et al (2009) and Dere et al (2013), the prior clinical and community studies (e.g., Weiss et al, 2009) only carried out frequency (i.e., classical test theory) analyses and did not include DIF analyses, which take into account degree of depressive symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…For depression specifically, work using multiple regression (Bimholz & Young, 2012) and nonparametric kernel-smoothing techniques (Santor, Ramsay, & Zuroff, 1994) has examined depressive symptom se verity scores and item bias between groups (i.e., female sexuality groups and males and females, respectively); however, these stud ies did not test for race or ethnicity differences. Another study (Dere et al, 2013) did examine race or ethnicity differences in depressive symptoms. With a clinical sample, Dere et al (2013) used the standardized mean difference technique to assess for DIF among Han-Chinese and European Canadian participants.…”
Section: The Diagnosticity Of Somatic and Psychological Symptomsmentioning
confidence: 99%